ANALISIS STRUKTUR, PERILAKU, DAN KINERJA PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA - Eka Fitriyanti (AKUNTABILITAS, 2015)
The crisis in 2007 which originates from the state of the united states have an impact on the banking sector in indonesia. Banking is the financial sector that is not in spite of the impact of the financial crisis global. In october 2009, three general bank conventional namely bank mandiri, bank negara indonesia, and bank rakyat indonesia liquidity assistance asked of each government 5 trillion rupiah (bank indonesia , 2009) In contrast to general sharia-based bank, during the period of the crisis can still show a business activity is better. The role of a syariah banking continued to increase it looks from the association of community funds that continue to increase from 2007 until years 2013. The condition of islamic banking industry in indonesia seen from the growth of third party funds, market share to the total third party funds indonesian banking, the performance of return on assets, office network development, and the number of workers kerjasudah fairly stable from the period 2007 to 2013 period. The development of syariah banking industry it can’t be good , there is still seen the gap between structural of syariah bank , where 2 bank controls more than 20 percent market share of total share of the third party funds syariah banking overall. The purpose of this research is analyzing the structure of the market in islamic banking industry in indonesia, analyse the influence on the performance of syariah bank market structure, and analyze the influence of behavior on the performance of syariah bank market in indonesia 2011-2014 year. The analysis used in this research is a method of data panel with simultaneous equations. This research result indicates that islamic banking industry in indonesia oligopoli presently, simultaneously the structure of markets influences behavior and conduct market effect on the performance of syariah bank market in indonesia 2011-2014 in the period.